A modified ceramic masterbatch and preparation method thereof
Through the combination of ceramic matrix, active ingredients, polyvinyl alcohol and silica nanoparticles and cutting-edge preparation technology, the brittleness, low toughness and oxide layer stability of modified ceramic masterbatches are solved, and efficient antibacterial and biocompatibility is achieved. , suitable for multifunctional applications and reduces the risk of environmental pollution.
Patent Information
- Application Number
- CN202410280871.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-03-12
AI Technical Summary
In practical applications, modified ceramic masterbatches face the inherent brittleness and low toughness of ceramics, difficulties in sintering and polarization, oxide layer stability problems, and the complexity and cost of the preparation process, especially the high level of rare earth elements. Cost and market scarcity, and the production process may cause environmental pollution.
Modified ceramic masterbatches composed of ceramic matrix, active ingredients, polyvinyl alcohol and silica nanoparticles are used to accurately control the material composition and microstructure through cutting-edge technologies such as sol-gel method, ball milling mixing and hot pressing sintering to improve machinery Performance and biological activity, reduce sintering temperature, enhance antibacterial properties, and form a dense coating by plasma spraying.
It significantly improves the antibacterial properties, biocompatibility and versatility of modified ceramic masterbatches, enhances mechanical properties and stability, reduces the risk of environmental pollution, and is suitable for medical, biomedical and environmental purification fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material science, and in particular to a modified ceramic masterbatch and a preparation method thereof. Background Art
[0002] Modified ceramics is a processing technology that improves the performance of traditional ceramic materials through methods such as element doping, composite material technology, surface modification, process optimization or nanotechnology. These modification methods can improve the mechanical strength, wear resistance, high temperature resistance, corrosion resistance and electrical properties of ceramics. For example, by adding rare earth elements or other metal elements to ceramics, their crystal structure and chemical composition can be changed; by utilizing the high specific surface area and activity of nanomaterials, the performance of ceramics can be improved through nanocomposites; surface modification technologies such as coatings or chemical treatments can enhance the wear resistance and corrosion resistance of ceramics; and optimizing sintering processes and heat treatment processes can control the microstructure of ceramics, such as grain size and porosity, thereby improving their overall performance. Modified ceramics have a wide range of applications, involving aerospace, automotive industry, electronic devices, biomedicine and energy and other industries, providing important material support for the development of modern industry and science and technology.
[0003] Modified ceramic masterbatch is a special additive that modifies ceramic materials by physical or chemical methods to improve or enhance the properties of ceramics. These modifications may include improving the mechanical strength, wear resistance, high temperature resistance, corrosion resistance, electrical properties, etc. Modified ceramic masterbatch usually consists of high concentrations of pigment particles, dispersing aids and additives, which play a vital role in the production process of ceramic products. Modified ceramic masterbatch has a wide range of applications and can be used in industries such as plastic containers, wires and cables, automotive parts, toys, etc. They play an important role in the plastics industry. By adding them to plastics, they can improve the physical and chemical properties of plastics and make them have more excellent performance. For example, modified masterbatch can provide a rich color selection, while having excellent light resistance, wash resistance, high temperature resistance and other characteristics.
[0004] Modified ceramic masterbatch has shown its unique application value in the fields of aerospace, electronic energy, environmental protection and safety, such as being used to prepare thermal structural materials that are resistant to high temperature, lightweight and resistant to oxidation and ablation, as well as environmentally friendly rubber and plastic products with flame retardant properties. However, these materials still face many challenges in practical applications, including the inherent brittleness and low toughness of ceramics, as well as difficulties in sintering and polarization. In addition, the stability of the oxide layer of ultra-high temperature ceramic composites is particularly prominent under high temperature or high and low temperature cycle conditions. The complexity and cost of the preparation process are also one of the factors limiting its widespread application, especially the high cost and market scarcity of certain rare earth elements. Environmental impact assessment cannot be ignored either, as the pollution that may be generated during the production process needs to be properly managed. Future research needs to consider environmental sustainability while improving material performance to overcome these challenges. Summary of the invention
[0005] In summary, in order to meet the needs of the market, the present invention proposes a modified ceramic masterbatch and a preparation method thereof, which can significantly improve the above-mentioned problems currently existing.
[0006] A modified ceramic masterbatch, composed of the following components in parts by weight: 90-100 parts of a ceramic matrix, 3-5 parts of an active ingredient, 0.8-1.2 parts of polyvinyl alcohol, and 0.3-0.7 parts of silicon dioxide nanoparticles;
[0007] Wherein, the preparation method of the silicon dioxide nanoparticles is as follows:
[0008] Tetraethoxysilane and anhydrous ethanol are uniformly mixed in a solid-liquid ratio of 1:1-5, and deionized water is added as a catalyst in a molar ratio of tetraethoxysilane:deionized water = 1:1-5. The reaction container is sealed and heated at a temperature of 150-200°C for 22-26 hours, and then the reaction container is naturally cooled to room temperature. The reaction liquid is taken out and centrifuged at a speed of 10000-15000 rpm to collect the precipitate. The precipitate is washed with deionized water and dried to constant weight under vacuum conditions at 70-80°C to obtain silica nanoparticles.
[0009] Preferably, the modified ceramic masterbatch is composed of the following components in parts by weight: 95 parts of ceramic matrix, 4 parts of active ingredients, 1 part of polyvinyl alcohol, and 0.5 parts of silicon dioxide nanoparticles.
[0010] In the formulation of this modified ceramic masterbatch, the ceramic matrix is the main component, usually composed of high-performance ceramic materials such as alumina, zirconia or silicon carbide, providing basic physical and chemical properties such as high hardness, wear resistance, high temperature resistance and corrosion resistance. Active ingredients, such as cephaladin and silver nanoparticles, are added to give the masterbatch specific biological activity or functionality, such as anti-inflammatory, antiviral and antibacterial properties. These active ingredients are evenly dispersed in the ceramic matrix to enhance the functionality of the material. Polyvinyl alcohol, as a dispersant and stabilizer, helps to improve the dispersion of active ingredients in the ceramic matrix, prevent agglomeration, and ensure the uniformity and consistency of the product. At the same time, the tiny pores that may be left during the sintering process can serve as release channels for active ingredients. The sol-gel method is used to synthesize silica nanoparticles, which is a technology that precisely controls the composition of materials at the molecular level and can produce high-purity and uniform nanoscale powders. This method converts tetraethoxysilane into silica nanoparticles through hydrolysis and polymerization reactions, and then obtains the final product through centrifugation and drying steps. As a flux, silica nanoparticles reduce the sintering temperature, promote the densification of materials, improve mechanical properties, and their high specific surface area helps disperse active ingredients. The synergistic effect of these components enables the modified ceramic masterbatch to have specific biological activity and functionality while maintaining the excellent properties of ceramic materials, and is suitable for medical, biomedical, environmental purification and other fields.
[0011] Preferably, the ceramic matrix is one or more of alumina, zirconium oxide, and silicon carbide.
[0012] Preferably, the ceramic matrix is composed of the following components in parts by weight: 4-8 parts of aluminum oxide, 2-4 parts of zirconium oxide, and 0.5-1.5 parts of silicon carbide.
[0013] Preferably, the ceramic matrix is composed of the following components in parts by weight: 6 parts of aluminum oxide, 3 parts of zirconium oxide, and 1 part of silicon carbide.
[0014] This composite ceramic matrix composed of alumina, zirconia and silicon carbide exhibits unique performance characteristics and advantages compared to conventional single ceramic matrices. First, this composite matrix combines the high hardness and wear resistance of alumina, the high toughness and fracture toughness of zirconia, and the high temperature stability and corrosion resistance of silicon carbide, thereby providing a material with better overall performance. This matrix exhibits excellent mechanical strength and durability under high pressure and extreme temperature conditions, making it suitable for extremely demanding industrial environments. Secondly, the composite matrix has a low coefficient of thermal expansion, which means that the material has better dimensional stability when the temperature changes, reducing the risk of cracking caused by thermal stress. In addition, the high degree of densification of this matrix helps to improve the corrosion resistance and chemical erosion resistance of the material, making it have a wide range of application potential in the chemical industry and aerospace fields. Finally, during the preparation of the composite ceramic matrix, its microstructure can be optimized by precisely controlling the sintering conditions, thereby further improving the overall performance of the material. These characteristics give the composite ceramic matrix a significant competitive advantage in the field of high-performance ceramic materials.
[0015] Preferably, the ceramic matrix preparation method is as follows:
[0016] A1: Use the sol-gel method to synthesize aluminum oxide, zirconium oxide, and silicon carbide nanoparticles. Use isopropyl aluminate as the precursor of aluminum oxide, tetrabutoxy zirconium as the precursor of zirconium oxide, and tetraethoxysilane as the precursor of silicon carbide. Place the three precursors in different containers and dissolve them in anhydrous ethanol. The container used to synthesize nano-scale aluminum oxide is container A, the container used to synthesize nano-scale zirconium oxide is container B, and the container used to synthesize nano-scale silicon carbide is container C. Add 100-500 mL of anhydrous ethanol to each of the three containers, stir until the precursors are dissolved, and set aside.
[0017] A2: Deionized water is slowly added to the container A to prepare a sol under the conditions of a hydrolysis ratio (molar ratio of water to precursor) of 2.8-3.2:1 and a stirring speed of 450-550 rpm, the sol is allowed to stand for 22-26 hours to obtain a gel A, and after vacuum drying at 75-85°C for 46-50 hours, the gel A is calcined at 950-1050°C for 1.8-2.2 hours, and ground for 2-4 hours under the conditions of a ball-to-material ratio of 10-30:1, a grinding speed of 200-500 rpm, and a grinding pressure of 0.5-2.0 MPa to obtain aluminum oxide nanoparticles;
[0018] A3: slowly adding hydrochloric acid to the container B, preparing a sol under the conditions of a hydrolysis ratio of 1.8-2.2:1, a pH of 1.8-2.2, and a stirring speed of 550-650 rpm, allowing the sol to stand for 46-50 hours to obtain a gel B, vacuum drying at 95-105°C for 70-74 hours, calcining the gel B at 1150-1250°C for 2.8-3.2 hours, and grinding for 2-4 hours under the conditions of a ball-to-material ratio of 10-30:1, a grinding speed of 200-500 rpm, and a grinding pressure of 0.5-2.0 MPa to obtain zirconium oxide nanoparticles;
[0019] A4: slowly adding sodium hydroxide to the container C, preparing a sol under the conditions of a hydrolysis ratio of 0.8-1.2:1, a pH of 11.8-12.2, and a stirring speed of 680-720 rpm, allowing the sol to stand for 22-26 hours to obtain a gel C, vacuum drying the gel C at 118-122° C. for 46-50 hours, calcining the gel C at 1450-1550° C. for 1.8-2.2 hours, and grinding the gel C for 2-4 hours under the conditions of a ball-to-material ratio of 10-30:1, a grinding speed of 200-500 rpm, and a grinding pressure of 0.5-2.0 MPa to obtain silicon carbide nanoparticles;
[0020] A5: Add the prepared alumina nanoparticles, zirconium oxide nanoparticles, and silicon carbide nanoparticles into a ball mill of a planetary ball mill, add grinding balls at a ball-to-material ratio of 18-22:1, add 90-110 mL of anhydrous ethanol and 0.8-1.2 g of polyvinyl alcohol, and perform ball milling at a rotation speed of 380-420 rpm for 22-26 hours. After the ball milling, dry at 55-65° C. for 22-26 hours to obtain mixed nanoparticles;
[0021] A6: Dry the mixed nanoparticles to constant weight, load them into a hot pressing sintering mold, and use a high-temperature hot pressing sintering furnace to perform hot pressing sintering under the conditions of a sintering temperature of 1400-1700°C, a heating rate of 5-10°C / s, a holding time of 1-4 hours, and a pressure of 20-50 MPa to obtain the ceramic matrix after cooling.
[0022] The ceramic matrix preparation method adopts cutting-edge technologies such as sol-gel method, ball milling, hot pressing sintering and plasma spraying. The sol-gel method allows the composition of the material to be precisely controlled at the molecular level, thereby obtaining high-purity and uniform nano-scale powders. The ball milling mixing technology achieves ultra-fine grinding and uniform mixing of powders through high-energy ball milling, thereby improving the dispersibility of the active ingredients. The hot pressing sintering technology achieves material densification at a lower temperature, maintains the stability of the active ingredients, and improves the mechanical strength of the masterbatch. The plasma spraying technology forms a uniform and dense coating on the surface of the ceramic masterbatch, enhancing the surface activity and biocompatibility. Compared with conventional processes, the advantage of this preparation method is that it can precisely control the microstructure of the material, improve the overall performance of the material, and enhance the functionality of the material through synergistic effects, such as antibacterial properties, so that it has a wider application potential in the fields of medical treatment, biomedicine and environmental purification. In addition, this method also helps to improve the environmental friendliness of the material because the encapsulation of the active ingredients in the ceramic matrix reduces direct exposure to the environment.
[0023] Preferably, the active ingredient is one or more of cephalaenopsis, silver nanoparticles, and copper sulfate.
[0024] Preferably, the active ingredient is composed of the following components in parts by weight: 3-5 parts of cephalaenopsis, 2-4 parts of silver nanoparticles, and 2-4 parts of copper sulfate.
[0025] Preferably, the active ingredient is composed of the following components in parts by weight: 4 parts of cepharanthin, 3 parts of silver nanoparticles, and 3 parts of copper sulfate.
[0026] As an alkaloid, cephalanthrin can bind to specific receptors on the cell membrane, affect the intracellular signal transduction pathway, inhibit bacterial growth or induce bacterial death. Silver nanoparticles can destroy the bacterial cell membrane, causing the cell contents to leak. At the same time, silver ions can bind to bacterial biomacromolecules such as DNA, proteins and enzymes, interfere with their functions, and cause bacterial death. When cephalanthrin and silver nanoparticles act on bacteria together, cephalanthrin may enhance the permeability of bacterial cell membranes, allowing more silver nanoparticles and silver ions to enter the cells, thereby enhancing the antibacterial effect. The copper ions in copper sulfate can act as cofactors for enzymes and affect the metabolic pathways of bacteria. At low concentrations, copper ions may promote the growth of some bacteria, but at higher concentrations, copper ions will inhibit bacterial growth because excessive copper ions can cause oxidative stress and DNA damage. When cephalanthrin and copper sulfate act together, cephalanthrin may enhance the antibacterial effect by inhibiting the bacterial defense mechanism, making copper ions more likely to have toxic effects on bacteria. Silver nanoparticles and copper ions both have antimicrobial activity, and they may damage bacterial cell structures and metabolic functions through different mechanisms. In some cases, silver nanoparticles and copper ions may form a synergistic effect on bacterial cell membranes, jointly leading to cell membrane damage and loss of function, thereby accelerating bacterial death. The specific mechanisms of these synergistic effects may involve a variety of biochemical processes, including cell membrane destruction, interference with intracellular signal transduction, inhibition of metabolic pathways, and increased oxidative stress.
[0027] Preferably, the active ingredient preparation method is as follows:
[0028] B1: preparing cephalaenopsis into a 0.8-1.2 mg / mL solution, preparing silver nanoparticles into a 0.8-1.2 mg / mL suspension, preparing copper sulfate into a 0.8-1.2 mg / mL solution, dispersing the silica nanoparticles in 180-220 mL of deionized water to obtain a silica nanoparticle suspension; adding the cephalaenopsis solution, the silver nanoparticle suspension and the copper sulfate solution to the silica nanoparticle suspension, while stirring with a magnetic stirrer at a speed of 480-520 rpm to ensure adequate mixing, and during the stirring process, slowly adding 0.8-1.2% w / v polyvinyl alcohol solution as a stabilizer to enhance the stability of the nanoparticles, and continuing stirring for 1.8-2.2 hours, collecting the precipitate by centrifugation, and drying at 58-62° C. for 22-26 hours to obtain composite nanoparticles;
[0029] B2: The composite nanoparticles are dispersed in a polyvinyl alcohol solution with a concentration of 0.8-1.2% w / v at a solid-liquid ratio of 1:48-52, and ultrasonic treatment is performed for 8-12 minutes to ensure uniform dispersion of the nanoparticles. After stirring at room temperature for 22-26 hours, 0.08-0.12% v / v glutaraldehyde is added as a cross-linking agent, and stirring is continued for 2 hours to achieve cross-linking of the polyvinyl alcohol; centrifugation is performed at 14000-16000 rpm for 28-32 minutes to remove unreacted polyvinyl alcohol and cross-linking agent, and the precipitate is collected, washed and dried to constant weight to obtain the active ingredient.
[0030] During the preparation of the active ingredient, cephaladin is formulated into a solution, silver nanoparticles are formulated into a suspension, and copper sulfate is formulated into a solution and mixed with silica nanoparticles to form composite nanoparticles. In this process, polyvinyl alcohol is added as a stabilizer to enhance the stability of the nanoparticles. Finally, the stability of the composite nanoparticles is further improved by ultrasonic treatment and glutaraldehyde cross-linking. The advantage of this preparation method is that it can ensure that the active ingredient is evenly dispersed in the nanocarrier, thereby improving its biological activity and stability. In addition, by controlling the size and surface properties of the nanoparticles, precise regulation of the release rate of the active ingredient can be achieved, which is crucial for drug delivery systems and biomedical applications.
[0031] Preferably, the method for preparing the modified ceramic masterbatch is as follows:
[0032] C6: Under the conditions of a ball milling speed of 280-320 rpm, a ball-to-material ratio of 8-12:1, and a ball milling time of 20-28 hours, the ceramic matrix and the active ingredient are mixed to obtain a mixture, and during the mixing process, a polyvinyl alcohol solution is gradually added to improve the dispersibility and stability of the mixture;
[0033] C7: adding silica nanoparticles to the mixture and continuing ball milling for 0.8-1.2 hours to ensure uniform mixing with the ceramic matrix and active ingredients;
[0034] C8: The ball-milled mixture is dried at 55-65°C for 20-28 hours to constant weight. Proper ventilation should be maintained during the drying process to prevent overheating of the material. The dried mixture is sieved through a sieving machine to remove oversized agglomerates and ensure uniform particle size distribution of the masterbatch.
[0035] C9: Hot pressing sintering is performed at a heating rate of 8-12°C / min, a holding time of 1.8-2.2 hours, and a temperature of 1500-1600°C to ensure material densification and phase change;
[0036] C10: Plasma spraying was performed using argon as the working gas, with a flow rate of 20-40 L / min, a gas pressure of 0.5-1.0 MPa, a spraying power of 20-50 kW, a spraying distance of 8-12 mm, a spraying speed of 0.5-2 m / min, and a spraying time of 4-60 minutes to improve surface activity and biocompatibility; after spraying, the ceramic masterbatch was allowed to cool naturally in the air to obtain a modified ceramic masterbatch.
[0037] In the process of preparing this modified ceramic masterbatch, firstly, precise formula design is used to ensure that the ceramic matrix, active ingredients, polyvinyl alcohol and silica nanoparticles are mixed in a predetermined ratio. This precise formula control helps to achieve the expected performance of the masterbatch. The application of high-energy ball milling technology effectively achieves ultrafine grinding and uniform mixing of powders, which is crucial for improving the dispersibility of active ingredients. Hot pressing sintering technology achieves material densification at a lower temperature, which helps to maintain the stability of active ingredients and improve the mechanical strength of the masterbatch. In addition, plasma spraying technology is used to form a uniform and dense coating on the surface of the ceramic masterbatch, which not only enhances surface activity and biocompatibility, but also improves wear and corrosion resistance. As a flux, silica nanoparticles can reduce the sintering temperature, promote material densification, and may improve the mechanical properties of the material. The application of these cutting-edge technologies not only improves the performance of the modified ceramic masterbatch, but also ensures its wide application potential in medical, biomedical, environmental purification and other fields.
[0038] In summary, the present invention has the following beneficial effects:
[0039] 1. Enhanced antimicrobial properties: By combining the broad-spectrum antimicrobial activity of silver nanoparticles with the anti-inflammatory and antiviral properties of cepharanthin, this masterbatch can provide a stronger antimicrobial effect against a variety of microorganisms, including bacteria, fungi and some viruses.
[0040] 2. Improved biocompatibility: Copper ions in copper sulfate can promote cell proliferation and tissue repair at appropriate concentrations. Combined with the biological activity of cephalaenopsis, it may improve the biocompatibility of the material, making it more suitable for medical and biomedical applications.
[0041] 3. Synergistic effect: These three active ingredients may work synergistically at the molecular level, enhancing each other’s effects. For example, cepharanthin may enhance the permeability of bacterial cell membranes, making it easier for silver nanoparticles and copper ions to enter the cells, thereby improving antibacterial efficiency.
[0042] 4. Multifunctionality: This masterbatch not only has antibacterial and anti-inflammatory properties, but can also be formulated to impart other functions, such as promoting bone tissue growth and enhancing the mechanical properties of materials, as needed.
[0043] 5. Stability and durability: By embedding the active ingredients into the ceramic matrix, its stability under various environmental conditions can be improved, while the release rate of the active ingredients can be controlled to ensure long-term effectiveness.
[0044] 6. Environmental friendliness: Compared with traditional antimicrobial agents, this composite active ingredient modified ceramic masterbatch may have lower environmental risks because the encapsulation of its active ingredients in the ceramic matrix can reduce direct exposure to the environment.
[0045] 7. Wide application potential: This masterbatch can be used in many fields such as medical implants, medical devices, biomedical coatings, antibacterial surface treatment, etc., providing a versatile, efficient and sustainable solution. DETAILED DESCRIPTION
[0046] In the following specific embodiments, the experimental method is as follows:
[0047] Compressive strength test: The universal material testing machine tests the compressive strength. The masterbatch sample is placed on the compression platform of the testing machine and the load is gradually increased at a rate of 0.5 mm / min until the sample is broken. The load-displacement curve recorded during this process will be used to determine the maximum load-bearing capacity of the masterbatch, thereby calculating the compressive strength, which is expressed in megapascals (MPa).
[0048] Fracture toughness test: A prefabricated crack is made on one side of the masterbatch sample, and then it is placed in a universal material testing machine and tested at the same loading rate. By recording the load-displacement curve during crack propagation, the critical value of fracture toughness (KIC) can be calculated in units of the square root of megapascals square meters (MPa m^0.5).
[0049] Antibacterial performance test: The experiment first prepared a certain concentration of Escherichia coli bacterial suspension on a sterile operating table, and then evenly coated it on the modified ceramic masterbatch coating at the bottom of the culture dish. After inoculation, the culture dish was placed in a constant temperature incubator set at 37°C for 24 hours. After the incubation, the size, morphology and number of colonies were observed and recorded, and compared with the control group without masterbatch. The antibacterial rate was calculated, that is, (the number of colonies in the control group - the number of colonies in the experimental group) / the number of colonies in the control group × 100%.
[0050] The present invention will be further described below in conjunction with specific examples. Specific examples are implemented under the premise of technical solutions of the present invention, and detailed implementation methods and operating procedures are provided. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following examples are usually carried out under normal conditions. Unless otherwise indicated, ratios and percentages are by weight.
[0051] Example 1
[0052] A modified ceramic masterbatch, composed of the following components in parts by weight: 95 parts of a ceramic matrix, 4 parts of an active ingredient, 1 part of polyvinyl alcohol, and 0.5 parts of silicon dioxide nanoparticles;
[0053] Wherein, the preparation method of the silicon dioxide nanoparticles is as follows:
[0054] Tetraethoxysilane and anhydrous ethanol were mixed uniformly at a solid-liquid ratio of 1:3, and deionized water was added as a catalyst at a molar ratio of tetraethoxysilane: deionized water = 1:3. The reaction container was sealed and heated at 175°C for 24 hours, and then the reaction container was naturally cooled to room temperature. The reaction liquid was taken out and centrifuged at a speed of 12500 rpm to collect the precipitate. The precipitate was washed with deionized water and dried to constant weight at 75°C under vacuum conditions to obtain silica nanoparticles.
[0055] The ceramic matrix is composed of the following components in parts by weight: 6 parts of aluminum oxide, 3 parts of zirconium oxide, and 1 part of silicon carbide.
[0056] The active ingredient is composed of the following components in parts by weight: 4 parts of cepharanthin, 3 parts of silver nanoparticles, and 3 parts of copper sulfate.
[0057] The ceramic matrix preparation method is as follows:
[0058] A1: Use the sol-gel method to synthesize aluminum oxide, zirconium oxide, and silicon carbide nanoparticles. Use isopropyl aluminate as the precursor of aluminum oxide, tetrabutoxy zirconium as the precursor of zirconium oxide, and tetraethoxysilane as the precursor of silicon carbide. Place the three precursors in different containers and dissolve them in anhydrous ethanol. The container used to synthesize nano-scale aluminum oxide is container A, the container used to synthesize nano-scale zirconium oxide is container B, and the container used to synthesize nano-scale silicon carbide is container C. Add 300 mL of anhydrous ethanol to each of the three containers, stir until the precursors are dissolved, and set aside.
[0059] A2: Deionized water was slowly added into the container A to prepare a sol at a hydrolysis ratio of 3:1 and a stirring speed of 500 rpm. The sol was allowed to stand for 24 hours to obtain a gel A. After vacuum drying at 80°C for 48 hours, the gel A was calcined at 1000°C for 2 hours, and then ground for 3 hours at a ball-to-material ratio of 20:1, a grinding speed of 350 rpm, and a grinding pressure of 1.3 MPa to obtain aluminum oxide nanoparticles.
[0060] A3: Slowly add hydrochloric acid to the container B to prepare a sol under the conditions of a hydrolysis ratio of 2:1, a pH of 2, and a stirring speed of 600 rpm. The sol is allowed to stand for 48 hours to obtain a gel B. After vacuum drying at 100°C for 72 hours, the gel B is calcined at 1200°C for 3 hours, and then ground for 3 hours at a ball-to-material ratio of 20:1, a grinding speed of 350 rpm, and a grinding pressure of 1.3 MPa to obtain zirconium oxide nanoparticles.
[0061] A4: Sodium hydroxide was slowly added into the container C to prepare a sol under the conditions of a hydrolysis ratio of 1:1, a pH of 12, and a stirring speed of 700 rpm. The sol was allowed to stand for 24 hours to obtain a gel C. After vacuum drying at 120°C for 48 hours, the gel C was calcined at 1500°C for 2 hours, and then ground for 3 hours under the conditions of a ball-to-material ratio of 20:1, a grinding speed of 350 rpm, and a grinding pressure of 1.3 MPa to obtain silicon carbide nanoparticles.
[0062] A5: Add grinding balls to the prepared alumina nanoparticles, zirconium oxide nanoparticles, and silicon carbide nanoparticles at a ball-to-material ratio of 20:1, add 100 mL of anhydrous ethanol and 1 g of polyvinyl alcohol, and ball-mill at a speed of 400 rpm for 24 hours. After ball-milling, dry at 60°C for 24 hours to obtain mixed nanoparticles;
[0063] A6: Dry the mixed nanoparticles to constant weight, load them into a hot pressing sintering mold, and perform hot pressing sintering at a sintering temperature of 1550°C, a heating rate of 7.5°C / s, a holding time of 2.5 hours, and a pressure of 35 MPa. After cooling, the ceramic matrix is obtained.
[0064] The active ingredient preparation method is as follows:
[0065] B1: Prepare cephalaenopsis into a 0.8-1.2 mg / mL solution, prepare silver nanoparticles into a 0.8-1.2 mg / mL suspension, prepare copper sulfate into a 0.8-1.2 mg / mL solution, and disperse the silica nanoparticles in 200 mL of deionized water to obtain a silica nanoparticle suspension; add the cephalaenopsis solution, the silver nanoparticle suspension and the copper sulfate solution to the silica nanoparticle suspension, and stir at 500 rpm to ensure sufficient mixing. During the stirring process, slowly add 1% w / v polyvinyl alcohol solution as a stabilizer, continue stirring for 2 hours, collect the precipitate by centrifugation, and dry at 60°C for 24 hours to obtain composite nanoparticles;
[0066] B2: The composite nanoparticles were dispersed in a 1% w / v polyvinyl alcohol solution at a solid-liquid ratio of 1:50, and ultrasonic treatment was performed for 10 minutes to ensure uniform dispersion of the nanoparticles. After stirring at room temperature for 24 hours, 0.1% v / v glutaraldehyde was added as a cross-linking agent, and stirring was continued for 2 hours; centrifugation was performed at 15,000 rpm for 30 minutes to remove unreacted polyvinyl alcohol and cross-linking agent, and the precipitate was collected, washed, and dried to constant weight to obtain the active ingredient.
[0067] The modified ceramic masterbatch preparation method is as follows:
[0068] C1: The ceramic matrix and the active ingredient were mixed under the conditions of a ball milling speed of 300 rpm, a ball-to-material ratio of 10:1, and a ball milling time of 24 hours to obtain a mixture. During the mixing process, the polyvinyl alcohol solution was gradually added;
[0069] C2: adding silica nanoparticles to the mixture and continuing ball milling for 1 hour;
[0070] C3: drying the ball-milled mixture at 60° C. for 24 hours to constant weight, and sieving the dried mixture to remove oversized agglomerates;
[0071] C4: the sieved mixture is hot pressed and sintered at a temperature of 1550° C. at a heating rate of 10° C. / min, a holding time of 2 hours, and a temperature of 1550° C.;
[0072] C5: Plasma spraying was performed under the conditions of using argon as the working gas, a flow rate of 30 L / min, a gas pressure of 0.75 MPa, a spraying power of 35 kW, a spraying distance of 10 mm, a spraying speed of 1.3 m / min, and a spraying time of 32 minutes to improve surface activity and biocompatibility; after spraying, the ceramic masterbatch was allowed to cool naturally in the air to obtain the modified ceramic masterbatch.
[0073] Example 2
[0074] A modified ceramic masterbatch, composed of the following components in parts by weight: 90 parts of a ceramic matrix, 3 parts of an active ingredient, 0.8 parts of polyvinyl alcohol, and 0.3 parts of silicon dioxide nanoparticles;
[0075] Wherein, the preparation method of the silicon dioxide nanoparticles is as follows:
[0076] Tetraethoxysilane and anhydrous ethanol were mixed uniformly at a solid-liquid ratio of 1:1, and deionized water was added as a catalyst at a molar ratio of tetraethoxysilane: deionized water = 1:1. The reaction container was sealed and heated at 150°C for 22 hours, and then the reaction container was naturally cooled to room temperature. The reaction liquid was taken out and centrifuged at a speed of 10,000 rpm to collect the precipitate. The precipitate was washed with deionized water and dried to constant weight at 70°C under vacuum conditions to obtain silica nanoparticles.
[0077] The ceramic matrix is composed of the following components in parts by weight: 4 parts of aluminum oxide, 2 parts of zirconium oxide, and 0.5 parts of silicon carbide.
[0078] The active ingredient is composed of the following components in parts by weight: 3 parts of cephalaenopsis, 2 parts of silver nanoparticles, and 2 parts of copper sulfate.
[0079] The ceramic matrix preparation method is as follows:
[0080] A1: Use the sol-gel method to synthesize aluminum oxide, zirconium oxide, and silicon carbide nanoparticles. Use isopropyl aluminate as the precursor of aluminum oxide, tetrabutoxy zirconium as the precursor of zirconium oxide, and tetraethoxysilane as the precursor of silicon carbide. Place the three precursors in different containers and dissolve them in anhydrous ethanol. The container used to synthesize nano-scale aluminum oxide is container A, the container used to synthesize nano-scale zirconium oxide is container B, and the container used to synthesize nano-scale silicon carbide is container C. Add 100 mL of anhydrous ethanol to each of the three containers, stir until the precursors are dissolved, and set aside.
[0081] A2: Deionized water was slowly added into the container A to prepare a sol at a hydrolysis ratio of 2.8:1 and a stirring speed of 450 rpm. The sol was allowed to stand for 22 hours to obtain a gel A. After vacuum drying at 75°C for 46 hours, the gel A was calcined at 950°C for 1.8 hours, and then ground at a ball-to-material ratio of 10:1, a grinding speed of 200 rpm, and a grinding pressure of 0.5 MPa for 2 hours to obtain aluminum oxide nanoparticles.
[0082] A3: Slowly add hydrochloric acid to the container B to prepare a sol under the conditions of a hydrolysis ratio of 1.8:1, a pH of 1.8, and a stirring speed of 550 rpm. The sol is allowed to stand for 46 hours to obtain a gel B. After vacuum drying at 95°C for 70 hours, the gel B is calcined at 1150°C for 2.8 hours, and then ground for 2 hours at a ball-to-material ratio of 10:1, a grinding speed of 200 rpm, and a grinding pressure of 0.5 MPa to obtain zirconium oxide nanoparticles.
[0083] A4: Sodium hydroxide was slowly added into the container C to prepare a sol under the conditions of a hydrolysis ratio of 0.8:1, a pH of 11.8 and a stirring speed of 680 rpm. The sol was allowed to stand for 22 hours to obtain a gel C. After vacuum drying at 118°C for 46 hours, the gel C was calcined at 1450°C for 1.8 hours, and then ground for 2 hours under the conditions of a ball-to-material ratio of 10:1, a grinding speed of 200 rpm and a grinding pressure of 0.5 MPa to obtain silicon carbide nanoparticles.
[0084] A5: Add grinding balls to the prepared alumina nanoparticles, zirconium oxide nanoparticles, and silicon carbide nanoparticles at a ball-to-material ratio of 18:1, add 90 mL of anhydrous ethanol and 0.8 g of polyvinyl alcohol, and ball mill at a rotation speed of 380 rpm for 22 hours. After the ball milling, dry at 55°C for 22 hours to obtain mixed nanoparticles;
[0085] A6: Dry the mixed nanoparticles to constant weight, load them into a hot pressing sintering mold, and perform hot pressing sintering at a sintering temperature of 1400°C, a heating rate of 5°C / s, a holding time of 1 hour, and a pressure of 20 MPa. After cooling, the ceramic matrix is obtained.
[0086] The active ingredient preparation method is as follows:
[0087] B1: Prepare cephalaenopsis into a 0.8-1.2 mg / mL solution, prepare silver nanoparticles into a 0.8-1.2 mg / mL suspension, prepare copper sulfate into a 0.8-1.2 mg / mL solution, and disperse the silica nanoparticles in 180 mL of deionized water to obtain a silica nanoparticle suspension; add the cephalaenopsis solution, the silver nanoparticle suspension, and the copper sulfate solution to the silica nanoparticle suspension, and stir at 480 rpm to ensure sufficient mixing. During the stirring process, slowly add 0.8% w / v polyvinyl alcohol solution as a stabilizer, continue stirring for 1.8 hours, collect the precipitate by centrifugation, and dry at 58°C for 22 hours to obtain composite nanoparticles;
[0088] B2: The composite nanoparticles were dispersed in a polyvinyl alcohol solution with a concentration of 0.8% w / v at a solid-liquid ratio of 1:48, and ultrasonic treatment was performed for 8 minutes to ensure uniform dispersion of the nanoparticles. After stirring at room temperature for 22 hours, 0.08% v / v glutaraldehyde was added as a cross-linking agent, and stirring was continued for 2 hours; centrifugation was performed at 14000 rpm for 28 minutes to remove unreacted polyvinyl alcohol and cross-linking agent, and the precipitate was collected, washed and dried to constant weight to obtain the active ingredient.
[0089] The modified ceramic masterbatch preparation method is as follows:
[0090] C1: The ceramic matrix and the active ingredient were mixed under the conditions of a ball milling speed of 280 rpm, a ball-to-material ratio of 8:1, and a ball milling time of 20 hours to obtain a mixture. During the mixing process, the polyvinyl alcohol solution was gradually added;
[0091] C2: adding silica nanoparticles to the mixture and continuing ball milling for 0.8 hours;
[0092] C3: drying the ball-milled mixture at 55° C. for 20 hours to constant weight, and sieving the dried mixture to remove oversized agglomerates;
[0093] C4: the sieved mixture is hot pressed and sintered at a temperature of 1500° C. at a heating rate of 8° C. / min, a holding time of 1.8 hours, and a temperature;
[0094] C5: Plasma spraying was performed under the conditions of using argon as the working gas, a flow rate of 20 L / min, a gas pressure of 0.5 MPa, a spraying power of 20 kW, a spraying distance of 8 mm, a spraying speed of 0.5 m / min, and a spraying time of 4 minutes to improve surface activity and biocompatibility; after spraying, the ceramic masterbatch was allowed to cool naturally in the air to obtain the modified ceramic masterbatch.
[0095] Example 3
[0096] A modified ceramic masterbatch, composed of the following components in parts by weight: 100 parts of a ceramic matrix, 5 parts of an active ingredient, 1.2 parts of polyvinyl alcohol, and 0.7 parts of silicon dioxide nanoparticles;
[0097] Wherein, the preparation method of the silicon dioxide nanoparticles is as follows:
[0098] Tetraethoxysilane and anhydrous ethanol were mixed evenly at a solid-liquid ratio of 1:5, and deionized water was added as a catalyst at a molar ratio of tetraethoxysilane: deionized water = 1:5. The reaction container was sealed and heated at 200°C for 26 hours, and then the reaction container was allowed to cool naturally to room temperature. The reaction liquid was taken out and centrifuged at a speed of 15000 rpm to collect the precipitate. The precipitate was washed with deionized water and dried to constant weight at 80°C under vacuum conditions to obtain silica nanoparticles.
[0099] The ceramic matrix is composed of the following components in parts by weight: 8 parts of aluminum oxide, 4 parts of zirconium oxide, and 1.5 parts of silicon carbide.
[0100] The active ingredient is composed of the following components in parts by weight: 5 parts of cephalaenopsis, 4 parts of silver nanoparticles, and 4 parts of copper sulfate.
[0101] The ceramic matrix preparation method is as follows:
[0102] A1: Use the sol-gel method to synthesize aluminum oxide, zirconium oxide, and silicon carbide nanoparticles. Use isopropyl aluminate as the precursor of aluminum oxide, tetrabutoxy zirconium as the precursor of zirconium oxide, and tetraethoxysilane as the precursor of silicon carbide. Place the three precursors in different containers and dissolve them in anhydrous ethanol. The container used to synthesize nano-scale aluminum oxide is container A, the container used to synthesize nano-scale zirconium oxide is container B, and the container used to synthesize nano-scale silicon carbide is container C. Add 500 mL of anhydrous ethanol to each of the three containers, stir until the precursors are dissolved, and set aside.
[0103] A2: Deionized water was slowly added into the container A to prepare a sol at a hydrolysis ratio of 3.2:1 and a stirring speed of 550 rpm. The sol was allowed to stand for 26 hours to obtain a gel A. After vacuum drying at 85°C for 50 hours, the gel A was calcined at 1050°C for 2.2 hours, and then ground at a ball-to-material ratio of 30:1, a grinding speed of 500 rpm, and a grinding pressure of 2.0 MPa for 4 hours to obtain aluminum oxide nanoparticles.
[0104] A3: Slowly add hydrochloric acid to the container B to prepare a sol under the conditions of a hydrolysis ratio of 2.2:1, a pH of 2.2, and a stirring speed of 650 rpm. The sol is allowed to stand for 50 hours to obtain a gel B. After vacuum drying at 105°C for 74 hours, the gel B is calcined at 1250°C for 3.2 hours, and then ground for 4 hours at a ball-to-material ratio of 30:1, a grinding speed of 500 rpm, and a grinding pressure of 2.0 MPa to obtain zirconium oxide nanoparticles.
[0105] A4: Sodium hydroxide was slowly added into the container C to prepare a sol under the conditions of a hydrolysis ratio of 1.2:1, a pH of 12.2 and a stirring speed of 720 rpm. The sol was allowed to stand for 26 hours to obtain a gel C. After vacuum drying at 122°C for 50 hours, the gel C was calcined at 1550°C for 2.2 hours, and then ground at a ball-to-material ratio of 30:1, a grinding speed of 500 rpm and a grinding pressure of 2.0 MPa for 4 hours to obtain silicon carbide nanoparticles.
[0106] A5: Add grinding balls to the prepared alumina nanoparticles, zirconium oxide nanoparticles, and silicon carbide nanoparticles at a ball-to-material ratio of 22:1, add 110 mL of anhydrous ethanol and 1.2 g of polyvinyl alcohol, and perform ball milling at a rotation speed of 420 rpm for 26 hours. After the ball milling, dry at 65°C for 26 hours to obtain mixed nanoparticles;
[0107] A6: Dry the mixed nanoparticles to constant weight, load them into a hot pressing sintering mold, and perform hot pressing sintering at a sintering temperature of 1700°C, a heating rate of 10°C / s, a holding time of 4 hours, and a pressure of 50 MPa. After cooling, the ceramic matrix is obtained.
[0108] The active ingredient preparation method is as follows:
[0109] B1: Prepare cephalaenopsis into a 0.8-1.2 mg / mL solution, prepare silver nanoparticles into a 0.8-1.2 mg / mL suspension, prepare copper sulfate into a 0.8-1.2 mg / mL solution, and disperse the silica nanoparticles in 220 mL of deionized water to obtain a silica nanoparticle suspension; add the cephalaenopsis solution, the silver nanoparticle suspension, and the copper sulfate solution to the silica nanoparticle suspension, and stir at a speed of 520 rpm to ensure sufficient mixing. During the stirring process, slowly add a 1.2% w / v polyvinyl alcohol solution as a stabilizer, continue stirring for 2.2 hours, collect the precipitate by centrifugation, and dry at 62°C for 26 hours to obtain composite nanoparticles;
[0110] B2: The composite nanoparticles were dispersed in a 1.2% w / v polyvinyl alcohol solution at a solid-liquid ratio of 1:52, and ultrasonic treatment was performed for 12 minutes to ensure uniform dispersion of the nanoparticles. After stirring at room temperature for 26 hours, 0.12% v / v glutaraldehyde was added as a cross-linking agent, and stirring was continued for 2 hours; centrifugation was performed at 16,000 rpm for 32 minutes to remove unreacted polyvinyl alcohol and cross-linking agent, and the precipitate was collected, washed, and dried to constant weight to obtain the active ingredient.
[0111] The modified ceramic masterbatch preparation method is as follows:
[0112] C1: The ceramic matrix and the active ingredient were mixed under the conditions of a ball milling speed of 320 rpm, a ball-to-material ratio of 12:1, and a ball milling time of 28 hours to obtain a mixture. During the mixing process, the polyvinyl alcohol solution was gradually added;
[0113] C2: adding silica nanoparticles to the mixture and continuing ball milling for 1.2 hours;
[0114] C3: drying the ball-milled mixture at 65° C. for 28 hours to constant weight, and sieving the dried mixture to remove oversized agglomerates;
[0115] C4: the sieved mixture is hot pressed and sintered at a temperature of 1600° C. at a heating rate of 12° C. / min, a holding time of 2.2 hours, and a temperature of 1200° C.;
[0116] C5: Plasma spraying was performed under the conditions of using argon as the working gas, a flow rate of 40 L / min, a gas pressure of 1.0 MPa, a spraying power of 50 kW, a spraying distance of 12 mm, a spraying speed of 2 m / min, and a spraying time of 60 minutes to improve surface activity and biocompatibility; after spraying, the ceramic masterbatch was allowed to cool naturally in the air to obtain the modified ceramic masterbatch.
[0117] Example 4
[0118] The difference from Example 1 is that the ceramic matrix is composed of the following components in parts by weight: 6 parts of aluminum oxide and 3 parts of zirconium oxide.
[0119] Example 5
[0120] The difference from Example 1 is that the ceramic matrix is composed of the following components in parts by weight: 6 parts of aluminum oxide and 1 part of silicon carbide.
[0121] Example 6
[0122] The difference from Example 1 is that the ceramic matrix is composed of the following components in parts by weight: 3 parts of zirconium oxide and 1 part of silicon carbide.
[0123] Example 7
[0124] The difference from Example 1 is that the active ingredient is composed of the following components in parts by weight: 4 parts of cephalaenopsis and 3 parts of silver nanoparticles.
[0125] Example 8
[0126] The difference from Example 1 is that the active ingredient consists of the following components in parts by weight: 4 parts of cepharanthin and 3 parts of copper sulfate.
[0127] Example 9
[0128] The difference from Example 1 is that the active ingredient consists of the following components in parts by weight: 3 parts of silver nanoparticles and 3 parts of copper sulfate.
[0129] Comparative Example 1
[0130] Unmodified ceramic masterbatch
[0131] Comparative Example 2
[0132] The difference from Example 1 is that it does not contain active ingredients.
[0133] Comparative Example 3
[0134] The difference from Example 1 is that polyvinyl alcohol is not contained.
[0135] Comparative Example 4
[0136] The difference from Example 1 is that no silicon dioxide nanoparticles are contained.
[0137] Experiment 1
[0138] Compressive strength test, fracture toughness test and antibacterial performance test were performed on Examples 1-9 and Comparative Examples 1-4.
[0139] The test results are shown in Table 1.
[0140]
[0141] As shown in Table 1, the data of Examples 1-9 show that a modified ceramic masterbatch of the present invention has stronger compressive strength, toughness and antibacterial effect than Comparative Example 1 (unmodified ceramic masterbatch). By comparing the experimental results of Comparative Examples 2-4 with those of Example 1, we can deeply understand the role of each component in the modified ceramic masterbatch. Example 1, as a benchmark, includes a ceramic matrix, active ingredients (cephalothin, silver nanoparticles and copper sulfate), polyvinyl alcohol and silica nanoparticles, and exhibits high compressive strength, fracture toughness and antibacterial rate. Comparative Example 2 lacks active ingredients, resulting in slightly higher compressive strength and fracture toughness than the unmodified ceramic masterbatch, but a significant decrease in antibacterial rate, which shows that active ingredients are essential for improving the mechanical properties and antibacterial properties of the material. The active ingredient may improve the compressive strength and fracture toughness by enhancing the microstructure of the material, such as grain boundary strengthening and crack deflection, and inhibit bacterial growth through direct antibacterial action. Comparative Example 3 lacks polyvinyl alcohol, and its compressive strength and fracture toughness are improved, but the antibacterial rate is significantly reduced, which shows that polyvinyl alcohol as a dispersant is essential for the uniform dispersion of active ingredients in the ceramic matrix, which helps to form a more uniform microstructure, thereby improving the mechanical properties of the material. Comparative Example 4 lacks silica nanoparticles. Although the compressive strength and fracture toughness are improved, the antibacterial rate is relatively low. This may be because silica nanoparticles as flux help to reduce the sintering temperature and promote material densification, thereby indirectly affecting the mechanical properties. These comparative analyses reveal the unique role of each component in the modified ceramic masterbatch and how they work together to improve the overall performance of the material through synergy.
[0142] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A modified ceramic masterbatch, consisting of the following components in parts by weight: 90-100 parts of ceramic matrix, 3-5 parts of active ingredients, 0.8-1.2 parts of polyvinyl alcohol, and 0.3-0.7 parts of silicon dioxide nanoparticles; wherein the preparation method of the silicon dioxide nanoparticles is as follows: Tetraethoxysilane and anhydrous ethanol are uniformly mixed at a material-liquid ratio of 1:1-5, deionized water is added as a catalyst at a molar ratio of tetraethoxysilane:deionized water = 1:1-5, the reaction container is sealed and heated at a temperature of 150-200°C for 22-26 hours, the reaction container is allowed to cool naturally to room temperature, the reaction liquid is taken out, centrifuged at a speed of 10000-15000 rpm, the precipitate is collected, the precipitate is washed with deionized water, and then dried to constant weight at 70-80°C under vacuum conditions to obtain silica nanoparticles; The active ingredient preparation method is as follows: B1: Prepare cephalaenopsis into a 0.8-1.2 mg / mL solution, prepare silver nanoparticles into a 0.8-1.2 mg / mL suspension, prepare copper sulfate into a 0.8-1.2 mg / mL solution, and disperse the silica nanoparticles in 180-220 mL of deionized water to obtain a silica nanoparticle suspension; add the cephalaenopsis solution, the silver nanoparticle suspension and the copper sulfate solution to the silica nanoparticle suspension, and stir at a speed of 480-520 rpm to ensure sufficient mixing. During the stirring process, slowly add 0.8-1.2% w / v polyvinyl alcohol solution as a stabilizer, continue stirring for 1.8-2.2 hours, collect the precipitate by centrifugation, and dry at 58-62° C. for 22-26 hours to obtain composite nanoparticles; B2: The composite nanoparticles are dispersed in a polyvinyl alcohol solution with a concentration of 0.8-1.2% w / v at a solid-liquid ratio of 1:48-52, and ultrasonic treatment is performed for 8-12 minutes to ensure uniform dispersion of the nanoparticles. After stirring at room temperature for 22-26 hours, 0.08-0.12% v / v glutaraldehyde is added as a cross-linking agent, and stirring is continued for 2 hours; centrifugation is performed at 14000-16000 rpm for 28-32 minutes to remove unreacted polyvinyl alcohol and cross-linking agent, and the precipitate is collected, washed, and dried to constant weight to obtain the active ingredient.
2. The modified ceramic masterbatch according to claim 1, characterized in that: The modified ceramic masterbatch is composed of the following components in parts by weight: 95 parts of ceramic matrix, 4 parts of active ingredients, 1 part of polyvinyl alcohol, and 0.5 parts of silicon dioxide nanoparticles.
3. A modified ceramic masterbatch according to claim 2, characterized in that: The ceramic matrix is composed of the following components in parts by weight: 4-8 parts of aluminum oxide, 2-4 parts of zirconium oxide, and 0.5-1.5 parts of silicon carbide.
4. The modified ceramic masterbatch according to claim 3, characterized in that: The ceramic matrix is composed of the following components in parts by weight: 6 parts of aluminum oxide, 3 parts of zirconium oxide, and 1 part of silicon carbide.
5. The modified ceramic masterbatch according to claim 4, characterized in that: The ceramic matrix preparation method is as follows: A1: Use the sol-gel method to synthesize aluminum oxide, zirconium oxide, and silicon carbide nanoparticles. Use isopropyl aluminate as the precursor of aluminum oxide, tetrabutoxy zirconium as the precursor of zirconium oxide, and tetraethoxysilane as the precursor of silicon carbide. Place the three precursors in different containers and dissolve them in anhydrous ethanol. The container used to synthesize nano-scale aluminum oxide is container A, the container used to synthesize nano-scale zirconium oxide is container B, and the container used to synthesize nano-scale silicon carbide is container C. Add 100-500 mL of anhydrous ethanol to each of the three containers, stir until the precursors are dissolved, and set aside. A2: Deionized water is slowly added to the container A to prepare a sol under the conditions of a hydrolysis ratio of 2.8-3.2:1 and a stirring speed of 450-550 rpm, the sol is allowed to stand for 22-26 hours to obtain a gel A, and after vacuum drying at 75-85°C for 46-50 hours, the gel A is calcined at 950-1050°C for 1.8-2.2 hours, and ground for 2-4 hours under the conditions of a ball-to-material ratio of 10-30:1, a grinding speed of 200-500 rpm, and a grinding pressure of 0.5-2.0 MPa to obtain aluminum oxide nanoparticles; A3: slowly adding hydrochloric acid to the container B, preparing a sol under the conditions of a hydrolysis ratio of 1.8-2.2:1, a pH of 1.8-2.2, and a stirring speed of 550-650 rpm, allowing the sol to stand for 46-50 hours to obtain a gel B, vacuum drying at 95-105°C for 70-74 hours, calcining the gel B at 1150-1250°C for 2.8-3.2 hours, and grinding for 2-4 hours under the conditions of a ball-to-material ratio of 10-30:1, a grinding speed of 200-500 rpm, and a grinding pressure of 0.5-2.0 MPa to obtain zirconium oxide nanoparticles; A4: slowly adding sodium hydroxide to the container C, preparing a sol under the conditions of a hydrolysis ratio of 0.8-1.2:1, a pH of 11.8-12.2, and a stirring speed of 680-720 rpm, allowing the sol to stand for 22-26 hours to obtain a gel C, vacuum drying the gel C at 118-122° C. for 46-50 hours, calcining the gel C at 1450-1550° C. for 1.8-2.2 hours, and grinding the gel C for 2-4 hours under the conditions of a ball-to-material ratio of 10-30:1, a grinding speed of 200-500 rpm, and a grinding pressure of 0.5-2.0 MPa to obtain silicon carbide nanoparticles; A5: Add grinding balls to the prepared alumina nanoparticles, zirconium oxide nanoparticles, and silicon carbide nanoparticles at a ball-to-material ratio of 18-22:1, add 90-110 mL of anhydrous ethanol and 0.8-1.2 g of polyvinyl alcohol, and perform ball milling at a rotation speed of 380-420 rpm for 22-26 hours. After the ball milling, dry at 55-65° C. for 22-26 hours to obtain mixed nanoparticles; A6: Dry the mixed nanoparticles to constant weight, load them into a hot pressing sintering mold, and perform hot pressing sintering at a sintering temperature of 1400-1700°C, a heating rate of 5-10°C / s, a holding time of 1-4 hours, and a pressure of 20-50 MPa. After cooling, the ceramic matrix is obtained.
6. A modified ceramic masterbatch according to any one of claims 1 to 5, characterized in that: The modified ceramic masterbatch preparation method is as follows: C1: Under the conditions of a ball milling speed of 280-320 rpm, a ball-to-material ratio of 8-12:1, and a ball milling time of 20-28 hours, the ceramic matrix and the active ingredient are mixed to obtain a mixture, and during the mixing process, the polyvinyl alcohol solution is gradually added; C2: adding silica nanoparticles to the mixture and continuing ball milling for 0.8-1.2 hours; C3: drying the ball-milled mixture at 55-65° C. for 20-28 hours to constant weight, and sieving the dried mixture to remove oversized agglomerates; C4: hot pressing and sintering the sieved mixture at a heating rate of 8-12°C / min, a holding time of 1.8-2.2 hours, and a temperature of 1500-1600°C; C5: Plasma spraying is performed under the conditions of using argon as the working gas, a flow rate of 20-40 L / min, a gas pressure of 0.5-1.0 MPa, a spraying power of 20-50 kW, a spraying distance of 8-12 mm, a spraying speed of 0.5-2 m / min, and a spraying time of 4-60 minutes to improve surface activity and biocompatibility; after spraying, the ceramic masterbatch is allowed to cool naturally in the air to obtain the modified ceramic masterbatch.
Citation Information
Patent Citations
Method for preparing transparent terbium gallium garnet ceramic
CN102976716A
Zirconia ceramic coating and preparation method thereof
CN109437892A